2022
DOI: 10.1186/s41983-022-00464-y
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychiatric lupus erythematosus in a cohort of Egyptian patients

Abstract: Background The neuropsychiatric lupus erythematosus (NPSLE) is a severe complication of systemic lupus erythematosus (SLE) that is characterized by a variety of neurological manifestations involving both central and peripheral nervous system with variable mechanisms. This study aimed to investigate the frequency of NPSLE and its relation to other clinical and laboratory findings in SLE patients. Results We retrieved the medical records of 134 SLE p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 52 publications
0
2
1
Order By: Relevance
“…The findings of this meta-analysis are in line with the recent meta-analysis conducted in the Swiss lupus cohort study (28.1%) ( 63 ). However, pooled overall prevalence of NPSLE in Pakistan is significantly lower than in the studies conducted in Switzerland at 56.3% ( 64 ) and Egypt at 50.7% ( 65 ). This discrepancy could be attributed to the differences in research methodology, sample size, and universal definition of NPSLE disorders.…”
Section: Discussioncontrasting
confidence: 62%
“…The findings of this meta-analysis are in line with the recent meta-analysis conducted in the Swiss lupus cohort study (28.1%) ( 63 ). However, pooled overall prevalence of NPSLE in Pakistan is significantly lower than in the studies conducted in Switzerland at 56.3% ( 64 ) and Egypt at 50.7% ( 65 ). This discrepancy could be attributed to the differences in research methodology, sample size, and universal definition of NPSLE disorders.…”
Section: Discussioncontrasting
confidence: 62%
“…The most common symptoms of adult SLE, according to a previous study, were headaches, which ranged from 20% to 40%; cognitive disorder, which was present in 10% to 20% of cases; seizures; and cerebrovascular disease, both of which were present in 7-10% of cases. Anxiety disorder was present in 4%-8% of cases [5,24]. Another study found that depression is the most prevalent NP condition, affecting 10.8% to 39.6% of SLE patients (6).…”
Section: Figurementioning
confidence: 97%
“…Neuropsychiatric SLE (NPSLE) is a presentation of SLE which influences psychiatric and neurologic systems [4] and one of the least recognised aspects is neurologic and psychiatric. It is frequently linked to a bad prognosis [5]. According to findings in the literature, NPSLE affects between 27% and 80% of persons with SLE [6][7][8][9].…”
Section: Introductionsmentioning
confidence: 99%